2022
DOI: 10.1111/dth.15308
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma: 2021 updated review of treatment

Abstract: Squamous cell carcinoma is the second most common cutaneous malignancy, requiring early diagnosis to prevent metastasis. Updated guidelines in the definition of clinical features, diagnostic modalities, grading, staging, surgical, and nonsurgical treatment methods are necessary. Diagnostic methods from biopsy, dermoscopy, and reflectance confocal microscopy have improved to include high-frequency ultrasonography, optical coherence tomography, and computed tomography. Non-surgical treatment methods include topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Current methods for treatments in cSCC are surgical excision, adjuvant therapy, radiotherapy, systemic treatment and so on, and more effective therapies are still explored. [26,27] CRISPR/Cas9 was considered an adaptive immune system of bacteria and archaea that protect these microbial from the foreign virus. Now, CRISPR-Cas9 is used as a powerful versatile technology for programmable gene editing in various fields.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current methods for treatments in cSCC are surgical excision, adjuvant therapy, radiotherapy, systemic treatment and so on, and more effective therapies are still explored. [26,27] CRISPR/Cas9 was considered an adaptive immune system of bacteria and archaea that protect these microbial from the foreign virus. Now, CRISPR-Cas9 is used as a powerful versatile technology for programmable gene editing in various fields.…”
Section: Discussionmentioning
confidence: 99%
“…Current methods for treatments in cSCC are surgical excision, adjuvant therapy, radiotherapy, systemic treatment and so on, and more effective therapies are still explored. [ 26,27 ]…”
Section: Discussionmentioning
confidence: 99%
“…The definition of clinical characteristics, diagnostic procedures, grading, staging, surgery, and non-invasive therapy must all be updated. Topical therapy, cryosurgery, photodynamic therapy, and radiation are among the non-surgical current therapies (Dreyfuss et al, 2022).…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…Cutaneous squamous cell carcinoma (SCC) is another common non-melanoma skin cancer that, unlike BCC, has the potential to metastasize. Early recognition and treatment are critical to reducing this risk, and actinic keratosis (AK) is considered a precursor lesion in SCC ( 46 ). Zhou et al., used an SD-OCT to image AK lesions of varying degrees in mice, which showed that the irregular wavy dermal-epidermal junction (DEJ) and persistent thickening of the epidermis are useful diagnostic parameters for AK.…”
Section: Application Of Oct In Oncologymentioning
confidence: 99%